COVID-19 Pandemic Significantly Decreases Acute Surgical Complaints. Issue 11 (November 2020) - Riley, John S.; Luks, Valerie L.; de Pina, Luis Filipe; Al Adas, Ziad; Stoecker, Jordan B.; Jackson, Benjamin M.; Braslow, Benjamin M.; Holena, Daniel N.
Background: The coronavirus disease 2019 (COVID-19) pandemic significantly reduced elective surgery in the United States, but the impact of COVID-19 on acute surgical complaints and acute care surgery is unknown. Study design: A retrospective review was performed of all surgical consults at the Hospital of the University of Pennsylvania in the 30 days prior to and 30 days following confirmation of the first COVID-19 patient at the institution. Consults to all divisions within general surgery were included. Results: Total surgical consult volume decreased by 43% in the post-COVID-19 period, with a significant reduction in the median daily consult volume from 14 to 8 ( P < .0001). Changes in consult volume by patient location, chief complaint, and surgical division were variable, in aggregate reflecting a disproportionate decrease among less acute surgical complaints. The percentage of consults resulting in surgical intervention remained equal in the 2 periods (31% vs 28%, odds ratio 0.85, 95% CI 0.61-1.21, P = .38) with most but not all operation types decreasing in frequency. The rise in the COVID-19 inpatient census led to increased consultation for vascular access, accommodated at our center by the creation of a new surgical procedures team. Conclusion: The COVID-19 pandemic significantly altered the landscape of acute surgical complaints at our large academic hospital. An appreciation of these trends may be helpful to other Departments of Surgery around the country as they deploy staff and allocate resources in the COVID-19 era.